2017
DOI: 10.1007/s41825-017-0004-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential and costs of reducing energy demand

Abstract: Determining the cost of energy saving measures and the magnitude of their potential application is the first and essential step to correctly design energy efficiency policies, which are in turn a keystone for energy transitions. This is particularly relevant for MENA countries, which feature energy intensities among the highest in the world. This paper presents a methodology for assessing reductions in energy demand based on expert evaluations; the methodology incorporates several improvements over previous si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In (1)(2)(3)(4)(5), the variables represent the following meanings: = Forget gate, = Input gate, = Output gate, ′ = Intermediate cell state, and = Cell state. These are the equations of gates and cell states of the LSTM.…”
Section: Casual Structure Of Proposed Rf-bi-lstm Hybrid Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In (1)(2)(3)(4)(5), the variables represent the following meanings: = Forget gate, = Input gate, = Output gate, ′ = Intermediate cell state, and = Cell state. These are the equations of gates and cell states of the LSTM.…”
Section: Casual Structure Of Proposed Rf-bi-lstm Hybrid Modelmentioning
confidence: 99%
“…In deregulated electricity markets, energy transactions and price of electricity are critically conditional on forecast electric loads. The operational cost may rise remarkably as an outcome of underestimating the energy demand [3].…”
Section: Introductionmentioning
confidence: 99%
“…They found that, even though the automatic light control was installed in the office, the occupant preferred to keep the blinds closed to prevent the automatic control system from switching off lights when there was adequate daylight. Besides, the cost of technologyrelated ECMs grows increasingly higher when no-and low-cost measures run out, and developers have to implement high-cost measures [7]. Due to these limitations of technological innovations and improvements, it is critical to adopt behaviour-related ECMs in order to yield further energy savings.…”
Section: Introductionmentioning
confidence: 99%
“…Cogeneration and polygeneration systems are an essential part of industrial production of materials and energies, consuming or generating heat, electricity, mechanical, and chemical energy [1,2]. Ambitious efforts of national and European institutions to reduce greenhouse gases emissions and to ensure sustainable industrial production [3][4][5][6][7][8][9] at the same time cannot be successfully met without increasing material and energy efficiency of the industry [10][11][12][13] by simultaneous energy, economic, environmental, and risk and safety optimization [14][15][16] of existing industrial cogeneration and polygeneration systems [17,18].…”
Section: Introductionmentioning
confidence: 99%